Assessment of carbon nanotubes (CNT) and fly ashes (FA) reinforced Al nanocomposites properties synthesised by powder metallurgy. (2020) - Devadiga, Udaya; Kumar Shetty, Sunil; Fernandes, Peter
Abstract: In this paper properties of Al metal matrix composites reinforced with carbon nanotubes (CNTs) and fly ashes (FAs) synthesized by powder metallurgy technique were investigated. Density, hardness and compression tests were carried out for the mechanical properties of the specimens. The experimental results showed that addition of FA increases hardness up to 8 wt. % and then decreases while hardness of the composite decreases with increase in CNT content. The results also showed that addition of FAs decreases density values while, addition of CNTs increases density of the composites. The compression strength properties of the composites improved over matrix material.With the aid of scanning electron microscope it was observed that CNTs and fly ashes were well dispersed and embedded in the matrix.XRD and EDS results showed no carbide formation or contamination during the processing of the composites